PTEN Deficiency in a Luminal ErbB-2 Mouse Model Results in Dramatic Acceleration of Mammary Tumorigenesis and Metastasis - Schade, Babette (American Society for Biochemistry and Molecular Biology, 2009)
Overexpression and/or amplification of the ErbB-2 oncogene as well as inactivation of the PTEN tumor suppressor are two important genetic events in human breast carcinogenesis. To address the biological impact of conditional inactivation of PTEN on ErbB-2-induced mammary tumorigenesis, we generated a novel transgenic mouse model that utilizes the murine mammary tumor virus (MMTV) promoter to directly couple expression of activated ErbB-2 and Cre recombinase to the same mammary epithelial cell (MMTV-NIC). Disruption of PTEN in the mammary epithelium of the MMTV-NIC model system dramatically accelerated the formation of multifocal and highly metastatic mammary tumors, which exhibited homogenous pathology. PTEN-deficient/NIC-induced tumorigenesis was associated with an increase in angiogenesis. Moreover, inactivation of PTEN in the MMTV-NIC mouse model resulted in hyperactivation of the phosphatidylinositol 3′-kinase/Akt signaling pathway. However, like the parental strain, tumors obtained from PTEN-deficient/NIC mice displayed histopathological and molecular features of the luminal subtype of primary human breast cancer. Taken together, our findings provide important implications in understanding the molecular determinants of mammary tumorigenesis driven by PTEN deficiency and ErbB-2 activation and could provide a valuable tool for testing the efficacy of therapeutic strategies that target these critical signaling pathways.